2020
DOI: 10.1007/s10798-020-09576-z
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of virtual design studio (VDS) use in STEM distance design education

Abstract: The use of virtual design studios (VDS) in practice-based STEM education is increasing but requires further research to inform understanding of student learning and success. This paper presents a longitudinal, large-scale study (3 years, 3000 students) of student behaviour in an online design studio used as part of a distance learning Design and Innovation qualification, within the School of Engineering and Innovation at The Open University (UK). The sample size and time period of the study is unprecedented an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
0
33
0
2
Order By: Relevance
“…However, these all researches also demonstrate that active interaction in an online environment has a bigger role than passive participation. Because, social presence is a necessity for teaching and cognitive presence to reach "higher-order thinking" (Armellini andDe Stefani, 2016 in Jones, Lotz andHolden, 2020). Moreover, in the same research, a student expresses the importance of active interaction that distance education is difficult, and with the interaction, it becomes easier.…”
Section: Situated Learning In Online Design Studiosmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these all researches also demonstrate that active interaction in an online environment has a bigger role than passive participation. Because, social presence is a necessity for teaching and cognitive presence to reach "higher-order thinking" (Armellini andDe Stefani, 2016 in Jones, Lotz andHolden, 2020). Moreover, in the same research, a student expresses the importance of active interaction that distance education is difficult, and with the interaction, it becomes easier.…”
Section: Situated Learning In Online Design Studiosmentioning
confidence: 98%
“…In the research, a positive correlation is viewed between students' visits to slots and success. Moreover, one of the students indicated that they can have a chance to making the right thing or not by comparing it with others' work (Jones et al, 2020). It is a positive part of online education that may not be sustained at face-to-face education.…”
Section: Situated Learning In Online Design Studiosmentioning
confidence: 99%
“…Numerous recent papers seek to examine virtual community of practice (VCoPs), technological platforms and tools in relation to online engagement, such as ‘bring your own device’ (BYOD) programmes, and distributed models of online learning (Chen et al 2020; Peeters & Pretorius 2020; Pozo Sánchez et al 2020). Innovative models for virtual studio learning have been developed by Pektaş (2015) and Jones et al (2020). The principles of a conventional in‐person art and design studio education are increasingly being redirected through a range of virtual channels in higher education.…”
Section: Studio As a Site For Learning And The Pivot To Online Educationmentioning
confidence: 99%
“…Technologies start to reshape teaching and design practices in the architectural design studio [20]. VDS can support interaction and complex social learning, leading to successful student outcomes and motivates students intrinsically [21]. In light of previous studies, a set of results was reached that can be summarized as shown in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%